Method of impedance analog of electromagnetic space for solving initial boundary value problems of electrodynamics - Ivanov, S.A.; Bogolyubov, A.N.; Sestroretskii, B.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2008)
The basic concepts of the method of impedance analog of electromagnetic space designed for numerical solving 2D- and 3D-problems of electrodynamics in time and frequency domains are considered. An approach to solve 2D-scalar initial boundary value problems and 3D-vector ones is briefly discusses. Some theoretical and practical results are given. This work was supported by the Russian Foundation for Basic Research (project N 06-01-00146). Keywords: method of impedance analog of electromagnetic space, TLM-method, numerical electrodynamics, time domain, initial boundary value problem, ITER, high-temperature plasma